2021
DOI: 10.1039/d0qo01188f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic intramolecular radical cyclization involved synergistic SET and HAT: synthesis of 3,3-difluoro-γ-lactams

Abstract: A mild and metal-free protocol for visible-light induced intramolecular radical cyclization of N-allyl(propargyl)-2-bromo-2,2-difluoro-N-arylacetamide has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Having in mind the mechanism proposed for the photocatalyzed processes reported previously, [9][10][11][12][13] we decided to run the reaction in the absence of any amines. Thus, 1a was irradiated in a mixture of THF/acetone or in THF and in the presence of fac-Ir(ppy) 3 alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having in mind the mechanism proposed for the photocatalyzed processes reported previously, [9][10][11][12][13] we decided to run the reaction in the absence of any amines. Thus, 1a was irradiated in a mixture of THF/acetone or in THF and in the presence of fac-Ir(ppy) 3 alone.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, to the best of our knowledge, there are few examples describing the synthesis of γ-lactams from α-haloamides under photoredox catalysis. Among these are: (a) the visible light photoredox catalyzed cyclization of α-chloroenamides in the presence of Ir(ppy) 2 (dtb-bpy)PF 6 , 9 (b) the synthesis of 3,3-difluoro-γ-lactams achieved from N -allyl(propargyl)-2-bromo-2,2-difluoroacetamides in the presence of fluorescein and under white LEDs, 10 and (c) the intermolecular photoredox catalytic atom transfer radical cyclization (ATRC) of 1,6-dienes and α-haloketones for the synthesis of 4-bromooctahydroindol-2-ones. 11 In addition, 3,3-disubstituted oxindoles were prepared under photoredox catalysis in the presence of fac -Ir(ppy) 3 12,15 and finally an intermolecular aminodifluoroalkylation of alkenes was reported in the synthesis of difluoro-γ-lactams using the same catalyst and blue LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, in 2018 and 2021, the report of synthesizing α,α‐difluoro‐γ‐lactams by visible‐light‐induced intramolecular radical cyclization or consecutive synthesis process appeared, as shown in Scheme 2 [9,10]. Sun, Su, Jin, and co‐workers showed that a variety of N ‐allyl(but‐3‐en‐1‐yl)‐2‐bromo‐2,2‐difluoroacetarylamines 1 and N ‐propargyl‐2‐bromo‐2,2‐difluoroacetarylamines 3 were well tolerated to provide the corresponding 4‐substituted α,α‐difluoro‐γ‐lactams 2 and 4 in moderate to excellent yields ( 2 : 39%–83%, 4 : 42%–89%) in the presence of fluorescein as photocatalyst, pentamethyl diethylenetriamine (PMDETA) as organoamine, and 1,2‐dichloroethane (DCE) as solvent at room temperature for 10–24 h [9].…”
Section: Synthesis Of αα‐Difluoro‐γ‐lactamsmentioning
confidence: 99%
“…Based on this, in 2018 and 2021, the report of synthesizing α,α‐difluoro‐γ‐lactams by visible‐light‐induced intramolecular radical cyclization or consecutive synthesis process appeared, as shown in Scheme 2 [9,10]. Sun, Su, Jin, and co‐workers showed that a variety of N ‐allyl(but‐3‐en‐1‐yl)‐2‐bromo‐2,2‐difluoroacetarylamines 1 and N ‐propargyl‐2‐bromo‐2,2‐difluoroacetarylamines 3 were well tolerated to provide the corresponding 4‐substituted α,α‐difluoro‐γ‐lactams 2 and 4 in moderate to excellent yields ( 2 : 39%–83%, 4 : 42%–89%) in the presence of fluorescein as photocatalyst, pentamethyl diethylenetriamine (PMDETA) as organoamine, and 1,2‐dichloroethane (DCE) as solvent at room temperature for 10–24 h [9]. In 2018, Wang et al used 2‐bromo‐2,2‐difluoro‐ N ‐alkyl‐ N ‐(1H‐indol‐3‐yl)acetamides 5 as raw materials and adopted visible‐light‐induced consecutive synthesis such as difluoromethylative dearomatization, hydroxylation, and oxidation to prepare the products gem ‐difluorinated spiro‐γ‐lactam oxindoles 6 in up to 85% yields [10].…”
Section: Synthesis Of αα‐Difluoro‐γ‐lactamsmentioning
confidence: 99%
See 1 more Smart Citation